Pengaruh Literasi Digital Terhadap Minat Membaca dan Menulis Anak Sekolah Dasar Selama Pandemi Covid-19 - Sahlatul Fatimah; Ibnu Muthi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research aims to examine the influence of digital literacy on elementary school students' interest in reading and writing during the Covid-19 pandemic. This research is qualitative research using the systematic literature review (SLR) method. Information is taken from the Google Scholar database for the last 5 years, viz. between 2020 and 2024 in full text format. The research results show that the Covid-19 pandemic has had a significant impact on elementary school students' education, especially in distance learning. Obstacles faced include lack of facilities, slow internet connection, and lack of direct interaction. Parents and teachers also face the challenges of costs, adapting to technology, and difficulty controlling and understanding students. However, online learning opens up opportunities for innovation and collaboration between parents, teachers and the community. Research also shows that the pandemic affects elementary school students' digital literacy and reading interest. Rahman found an increase in reading ability despite obstacles. Mirnawati identified the challenges and opportunities of online learning. Siroj noted that good digital literacy increases interest in reading. Andarini concluded that digital literacy at the UPI Serang Pilot Laboratory Elementary School was going quite well. Salsabillah revealed the negative impact of online learning on literacy and numeracy. Ayuniar highlighted the important role of teachers in teaching reading skills. Solahudin identified internal and external factors that influence students' reading interest. Anam emphasized the need for educational updates and technological support during the pandemic.